Analysis of available transfer capability (ATC) of transmission system using MATLAB - Lim, Choon Seong (Universiti Malaysia Perlis, 2009)
In deregulating power systems, Available transfer capability (ATC) determination and calculation are important for efficient and competitive utility operation. Total transfer Capability (TTC) is the basic measure for evaluating Available transfer capability (ATC). Available transfer capability (ATC) is relatively new concept and plays an increasingly significant role in the power industry deregulated environment. Calculating it involves many technical challenges including total transfer capability calculation, transmission capability margins and probabilistic ATC calculation. The transmission reliability margin is implemented by making any one of the transmission lines as out of order at a time. The proposed computation procedure of available transfer capability with margins was applied to test the performance of the methodologies and programs for IEEE-5 bus system, IEEE-9 bus system, IEEE-11 bus system, IEEE-26 bus system and IEEE-30 bus system. The solutions obtained are quite encouraging and useful in the present deregulated environment. The result were compared with other procedures for accuracy